Bishop of Calcutta to the Earl of Chichester, Bishop's Palace, Calcutta, Feb. 27, 1839 - University of Birmingham Library; Adam Matthew Digital (Adam Matthew Digital, 1839)
Documents: letter to the President of the Church Missionary Society relating the impact of missionary contacts in 1838; letter, Mr. J.W. Alexander to the Lay Secretary, Calcutta, March 9 1839; Minutes of Special Meeting of the Calcutta Corr. Committee, Feb. 27, 1839